A Gaming Laboratory for Understanding Strategic Behavior in Power Markets. Issue 9 (2022) - Korepanov, Vsevolod; Pozo, David; Korgin, Nikolay
Abstract: Results of four-year experimental trials of a Gaming Lab for understanding power markets are presented in here. The main goal of Gaming Lab was to illustrate the effects of strategic behavior on electricity markets, recognize pricing mechanisms and analyse the issues that emerge from competitive electricity markets. Evidences for reproducibility of obtained results of experimental gaming are provided. Different scenarios for conducting the developed series of games are described and compared. We finally provide recommendations on Gaming Lab implementation and future developments that could enhance the Gaming Lab.